The impact of herbivorous insect on leaves of mangrove species Rhizophora stylosa and its relation to leaf nutrient level - INDAH TRISNAWATI; MUKHAMMAD MURYONO; ISKA DESMAWATI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Trisnawati I, Muryono M, Desmawati I. 2019. The impact of herbivorous insect on leaves of mangrove species Rhizophora stylosa and its relation to leaf nutrient level. Biodiversitas 20: 1409-1415. Intertidal mangrove ecosystem is a very unique ecosystem which is under threat due to anthropogenic disturbances like land conversion to promote paddy cultivation and aquaculture and pollution. Increased nutrient loading from human activities is expected to have stronger responses to both mangroves and their associated herbivores. This research is aimed to investigate vulnerability of mangroves caused by herbivory of herbivorous insects, focusing on the diversity and abundance of herbivorous insects, the level of mangrove leaf damage and its relation to nutrient levels within leaves in term of nitrogen, phosphorus, potassium and water content. We observed mangrove habitats located around Institut Teknologi Sepuluh November (ITS) Campus in Surabaya, East Java dominated by Rhizophora vegetation. Herbivorous insects showed individual abundance of 15.15% of the total insects found in mangroves around the studied areas. The area of relative leaf damage in Rhizophora stylosa leaves tended to be high in sapling habitus (11.96-24.56%) compared to tree habitus (6.97-16.71%). One way ANOVA showed non-significant difference in leaf area damaged between sapling and tree habitus (F = 0.099, p-0.75), and percentage of herbivory between saplings and trees (F = 0.0007, p-0.98). Concentrations of potassium (K) was significantly higher in tree than sapling habitus, whereas leaf nutrient phosporous was significantly higher in sapling than tree habitus. Other leaf nutrients (total nitrogen and water) were relatively the same in both habitus. However, saplings contained more feeding deterrent tannins than trees. Leaf age is thought to be related to higher leaf palatability and insect herbivore nutrition in younger leaves, represented by sapling habitus.